Using integrated alternative assessment to explore essay writing skills: An insight into authentic instructional dashboards - Gebremariam, Hailay Tesfay; Tessema, Marew Alemu; Kahsay, Mulugeta Teka; Mulugeta, Zeritu Asfaw; Ambaye, Tsegaberhan Wodaj; Mulatu, Amare Teshome (Social sciences & humanities open, 2025)
Many undergraduate students struggle with developing their essay writing skills (EWS). On the other hand, studies have noted that teachers tend to rely on traditional instructional dashboards including assessments in writing classrooms. However, using traditional assessment (TA) may not accurately assess students' abilities, resulting in gaps in understanding and areas for improvement. This study aims to evaluate the effectiveness of Integrated Alternative Assessments (IAAs) in assessing university students' EWS. A counterbalanced design was utilized, involving two groups with two phases of implementation. Forty-seven first-year students participated in the study. Data collected included EWS evaluations from both implementation phases and student portfolios. Statistical analysis, including independent samples t-tests, MANOVA, and ANCOVA, was used to compare EWS differences between the experimental and control groups. Qualitative data from student portfolio annotations were also analyzed alongside quantitative data. Results indicated statistically significant differences (p < 0.05) in EWS mean scores between the experimental and control groups in both phases, with no significant differences after the two intervention phases between the two groups. Qualitative data supported the quantitative findings, emphasizing the importance of IAAs in improving EWS. This study suggests that IAAs are effective methods for enhancing students' EWS skills and recommends integrating EWS with IAAs.